The VPQ scheduler in access point for VoIP over WLAN - Nisar, Kashif; Hassan, Suhaidi (2011)
The Voice over Internet Protocol (VoIP) application has observed the fastest growth in the world of telecommunication.VoIP is seen as a short-term and long-trem transmission for voice and audio traffic. Meanwhile, VoIP is moving on Wireless Local Area Networks (WLANs) based on IEEE 802.11 standards.Currently, there are many packet scheduling algorithms for real-time transmission over network.Unfortunately, the current scheduling will not be able to handle the VoIP packets with the proper manner and they have some drawbacks over real-time applications.The objective of this research is to propose a new Voice Priority Queue (VPQ) packet scheduling and algorithm to ensure more throughput, fairness and efficient packet scheduling for VoIP performance of queues and traffics.A new scheduler flexible which is capable of satisfying the VoIP traffic flows.Experimental topologies on NS-2 network simulator were analyzed for voice traffic. Preliminary results show that this can achieve maximum and more accurate VoIP quality throughput and fairness index in access point for VoIP over WLANs.We verified and validated VPQ an extensive experimental simulation study under various traffic flows over WLANs.